(untitled) (Journal of the Bangladesh Agricultural University, 2020)
The objectives of this study were to know the growth performance of graded Brahman calves, the phenotypic and genetic correlations between different growth traits and factors related to growth performance of Brahman graded calves in selected areas of Mymensingh district. Data on 422 Brahman graded calves were collected under the project entitled “Genetic improvement of indigenous cattle for beef production through crossing with Brahman cattle by farmers’ participatory breeding approach in Bangladesh” under the department of Animal Breeding and Genetics, BAU, Mymensingh. Statistical analyses of all the parameters were done using Statistical Analysis System (SAS). The growth performance and average daily gain of male calves were higher than those in female calves at different growth stages. The highest birth weight and weight at different stages of calves were higher in Bhabakhali and lowest in Dowhakhula area. Sex and area had significant effect (p<0.05) on different growth traits of Brahman crossbred calves. Breeding bull had significant effect (p<0.05) on nine-month and twelve weight and average daily gain from birth up to twelve month of age. Feeding system had significant effect (p<0.05) on different growth traits. Improve feeding would have positive impact on growth performance quite natural. Growth traits were positively correlated to each other and strong phenotypic correlations were observed between weight at nine and twelvemonth (0.95), six- and twelve-month (0.94) and six- and nine-month (0.93). It may be concluded that further study with larger sample sizes covering more factors related to growth performance of graded Brahman calves would be required to draw a better conclusion in this regard. J Bangladesh Agril Univ 18(2): 435–441, 2020 https://doi.org/10.5455/JBAU.73448